Mothers and others: transgender birth, birth registration and the rights of the child, with a focus on the United Kingdom and South Africa - SlothNielsen, J; Sloth-Nielsen, R (SAGE Publications, 2020)
The review concerns the position of the identification as ‘mother’ or ‘father’ of trans persons who give birth. This matter has occupied courts in the United Kingdom, Germany, Brazil and Sweden recently, and could well arise in South Africa, our country of origin. The first part of the discussion relates to a claim of a trans man who gave birth to be registered as the father of the child. The legal situation in South Africa and the United Kingdom is compared, and particular focus is placed on the meaning of ‘mother’. A second issue for discussion relates to the right of the child born to a trans person to birth registration, notably, what the child’s interests are in relation to his or her parent’s identification details on his or her birth certificate. We conclude that the gender identity of the trans parent must be the primary factor determining his or her registration as a parent on the birth certificate, and that this solution also better serves the child’s best interests.